This I Believe - Isaacs, Stanley M. (Stanley Myer) (Tufts Archival Research Center, 2006)
Stanley Isaacs talks about his dedication and enthusiasm for politics and civic engagement and expresses how his faith in judaism supports his beliefs in democratic values like liberty and individuality.